KINERJA DINAS LINGKUNGAN HIDUP DALAM PENGELOLAAN SAMPAH DI KOTA MANADO - WAHYUNI, SRI; TAMPI, GUSTAAF BUDI; MAMBO, RULLY (Sam Ratulangi University, 2017)
Abstract: Population and community dietary changes cause the increase of the volumes of type, and characteristic of theincreasingly diverse garbage waste management. Based on the problems of Research aims to know the performance ofthe Department of the environment in the waste management in the city of Manado.This study uses qualitative methods with selected informants consisting of Chairman, officials of the competent officials/staff/ implementation, and how the garbage workers in the service of the Environment Manado as well as the community.Data collection techniques used are interviews, observation and documentation. Qualitative data were analysed withdescriptive narrative supported by primary and secondary data.The results showed that the performance of the related Department of the environment in the waste management in the cityof Manado has shown a fairly good results, in terms of productivity can be seen already very good views of the goals set andthe effort to realize the goal, among others, with the application of law socialization, adds to the operational personnelhygiene and the granting of construction on the importance of environmental hygiene in order to materialize the city ofManado in a healthy, comfortable, clean, healthy and free of waste by improving the quality of service sothat waste treatment system Manado city becomes